2019
DOI: 10.3847/1538-3881/ab36b5
|View full text |Cite
|
Sign up to set email alerts
|

Two New HATNet Hot Jupiters around A Stars and the First Glimpse at the Occurrence Rate of Hot Jupiters from TESS

Abstract: Wide-field surveys for transiting planets are well suited to searching diverse stellar populations, enabling a better understanding of the link between the properties of planets and their parent stars. We report the discovery of HAT-P-69 b (TOI 625.01) and HAT-P-70 b (TOI 624.01), two new hot Jupiters around A stars from the Hungarian-made Automated Telescope Network (HATNet) survey that have also been observed by the Transiting Exoplanet Survey Satellite. HAT-P-69 b has a mass of-+ 3.58 0.58 0.58 M Jup and a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
92
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 111 publications
4
92
2
Order By: Relevance
“…The transits of KELT-9b show significant deviations from the typical transit light-curve shape. These asymmetries are attributable to the gravity-darkened photosphere of the rapidly rotating host star and have been reported for a handful of other transiting systems with hot host stars, including Kepler-13A (Barnes et al 2011), Kepler-462 (Ahlers et al 2015), HAT-P-70 (Zhou et al 2019), and MASCARA-4 (Ahlers et al 2020b). A detailed, dedicated analysis of the gravity-darkened transit of KELT-9b in TESS photometry is described in Ahlers et al (2020a).…”
Section: Tess Light Curvementioning
confidence: 66%
“…The transits of KELT-9b show significant deviations from the typical transit light-curve shape. These asymmetries are attributable to the gravity-darkened photosphere of the rapidly rotating host star and have been reported for a handful of other transiting systems with hot host stars, including Kepler-13A (Barnes et al 2011), Kepler-462 (Ahlers et al 2015), HAT-P-70 (Zhou et al 2019), and MASCARA-4 (Ahlers et al 2020b). A detailed, dedicated analysis of the gravity-darkened transit of KELT-9b in TESS photometry is described in Ahlers et al (2020a).…”
Section: Tess Light Curvementioning
confidence: 66%
“…KELT-9 b is an especially interesting target for hot Jupiter research. In its polar orbit, KELT-9 b follows the trend that gas giants around high-mass stars are frequently spin-orbit misaligned (e.g., Winn et al 2010;Albrecht et al 2012;Winn & Fabrycky 2015;Zhou et al 2019). Its high dayside temperature provides excellent opportunities for phase curve and secondary eclipse analyses (Hooton et al 2018;Wong et al 2019;Mansfield et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To date, five new hot Jupiters initially detected by TESS have been confirmed: HD 202772A b (Wang et al 2019), HD 2685 b (Jones et al 2019), TOI 150 b (Cañas et al 2019a;Kossakowski et al 2019), HD 271181 b (Kossakowski et al 2019), and TOI 172 b (Rodriguez et al 2019). Additionally, the HATNet survey (Bakos et al 2004) detected two transiting hot Jupiter candidates in 2010, HATS-P-69 b and HATS-P-70 b, which were later observed by TESS, leading to their confirmation (Zhou et al 2019).…”
Section: Introductionmentioning
confidence: 83%
“…Our empirical knowledge of hot Jupiters is based on the foundation of our small but growing sample of these worlds (currently numbering ∼250). While small, rocky planets are understood to be present, on average, around every star (e.g., Fressin et al 2013;Petigura et al 2018), various studies have found that on the order of only ∼0.5% of stars host a hot Jupiter (e.g., Howard et al 2012;Petigura et al 2018;Zhou et al 2019), ∼10% of which will have a geometry resulting in a visible transit. Transiting hot Jupiters are therefore intrinsically rare; so, given the broad and abiding questions surrounding them, there is value in each additional example found, particularly around stars that are amenable to follow-up observations.…”
Section: Introductionmentioning
confidence: 99%